Removal of Copper and Magnesium Cations from Aqueous Solutions by Clinoptilolite Zeolite Adsorption. Issue 1 (May 2021) - Aziz, R A; Fauzi, N F N; Salleh, M N; Saleh, M
Abstract: The aim of this study is to determine the potentials of clinoptilolite zeolite in removing selected heavy metals, that are copper and magnesium in aqueous solutions. The removal of both metal cations has been studied by using the batch techniques. Three experimental variables were carried out under predetermined conditions of contact time (20 – 100 minutes), effect of dosage (0.20 – 1.00 gram), and effect of pH solution (pH 2 to 10). Adsorption capacity of zeolite towards heavy metal removal was then determined at various initial concentrations of metal ions between 20 to 100 ppm. Results obtained shows that adsorption of Cu 2+ and Mg 2+ on zeolite has been shown to depend significantly on the pH, adsorbent amount and contact time. The significant value of pH was reached at pH 6, followed by 1 hour of contact time for 1 gram of adsorbent; for both metal ions studied. Studies on the rate of uptake of heavy metal ions by the zeolite indicated that the process was quite rapid and maximum adsorption occurred within the first hour of contact. The results show that high silica zeolite such as clinoptilolite is a promising adsorbent as they combine high adsorption capacities and molecular sieve properties.